Optimizing Congregational Prayer in Building Students' Religious Character at Madrasah Aliyah Jambi Laboratory - Raezli Jupindi; Muhammad Fadhil (Lembaga Bale Literasi, 2025)
The formation of students' religious character faces challenges due to social and digital changes, so religious education is not enough to be done through conceptual learning alone; it also requires consistent habituation. At the Jambi Laboratory MA, congregational Zuhur prayers have become part of the religious culture of madrasas, but their effectiveness in internalizing religious character needs to be studied. This study aims to analyze the implementation, optimization strategies, internalization process, impacts, and factors that support and inhibit congregational prayer in building students' religious character. This study uses a qualitative approach with a case study design. Data were obtained through observation, interviews, and documentation involving madrasah heads, teachers, religious activity coaches, homeroom teachers, and students. The validity of the data was strengthened through triangulation of sources and techniques, while the analysis used Miles and Huberman's interactive models. Congregational Zuhur prayers are carried out routinely and in an orderly manner through mandatory rules, supervision, monitoring, coaching, motivation, and providing religious understanding. Internalization takes place through three stages, namely obligation, habituation, and awareness. The main impact can be seen in increasing discipline, responsibility, obedience, togetherness, care, and awareness of worship. Optimizing congregational prayer is a strategy for building religious character if it is supported by continuous habituation, example, involvement of madrasah residents, and adequate facilities.